Effect of climatic factor that influence the population dynamics of Brown Planthopper, Nilaparavata lugens / Nur Shakiera Jusoh - Jusoh, Nur Shakiera (Faculty of Plantation and Agrotechnology, 2019)
Brown plant hopper is major pest that contribute of low productivity of the rice and it damage by feeds directly on the growing plant by sucking the phloem sap, hopper burn and it transmit the grassy stunt disease. This study was conducted to determine abundance of Brown Planthopper (BPH) in paddy field and the relationship between climatic factor such as temperature, rainfall and relative humidity. The data sampling was conducted from 11th July 2018 until 10th August 2018 was covered five weeks of data collection period in Bukit Lintang, Malacca. An experiment was conducted on 1 ha of plot field by using quadrate of 1m x 1m and set up randomly. Abundance of BPH revealed that BPH population was high from week one until week five. By using the correlation and regression analysis, the results indicated that abundance of BPH revealed that BPH population was high from week one until week five. The population of BPH was positively correlated (weak relationship) to rainfall where as a negative correlation (very weak relationship) was found to temperature and relative humidity. The independent variables such as temperature, relative humidity and rainfall are 7.10% influence the BPH population during data collection periods.